THE RELATIONSHIP BETWEEN THE DIAMETER OF THE ATRIAL SEPTAL DEFECT AND THE ENLARGEMENT OF RIGHT VENTRICLE OF THE HEART - , SREE SHANTHA KUMARAN, Dr. Lucia Krisdinarti, SpPD, SpJP ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: ASD is the defect in the septum between the atriums of the heart. Atrial Septal Defect (ASD) is a congenital heart disease that allows blood to flow from the left atrium into the right atrium, and occasionally from the right atrium to the left atrium. There are three most common types of ASD which includes patent foramen ovale (ostium secundum),ostium primum and sinus venosus. The diameter of ASD can cause the right ventricle enlargement due to the overload of blood volume in the right atrium and eventually in the right ventricle.Intervention should be done in those patients with ASD so that it can prevent heart failure. Objective: The objective of this research study is to find out the relationship between the diameter of the atrial septal defect and enlargement of the right ventricle of the heart. Method: The study done was an observational study using the cross-sectional retrospective design. The data were obtained from the medical record registries of adult ASD patients diagnosed in Department of Cardiology and Vascular Medicine, Faculty of Medicine, Gadjah Mada University Dr.Sardjito Hospital. The time frame to complete this research was from September 2013 till January 2014. The population taken for this research was patients diagnosed with atrial septal defect from Department of Cardiology and Vascular Medicine, Faculty of Medicine, Gadjah Mada University Dr.Sardjito Hospital, Yogyakarta from July 2012 till October 2013 and obeyed the inclusion and exclusion criteria. Results: The study shows that a significant p value which is 0.012 (p value < 0.05) between the diameter of atrial septal defect and the enlargement of the right ventricle. There is a correlation between the diameter of atrial septal defect and the right ventricle enlargement of the heart. The r value is 0.244. Besides that, the confounding variables in the study are age,sex and the mean pulmonary arterial pressure. All the three confounding factors does not confound significantly to the study. Conclusion: This study shows a significant relationship between the diameter of atrial septal defect and the enlargement of the right ventricle. The larger the diameter of the atrial septal defect, the bigger the enlargement of the right ventricle. It shows a positive relationship between the diameter of the atrial septal defect and the enlargement of the right ventricle of the heart.